2019
DOI: 10.1111/tid.13106
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with cytomegalovirus infection after the treatment of acute rejection during the first year in kidney transplant recipients receiving preemptive therapy

Abstract: There have been progressive and considerable improvements in the early management of kidney transplant recipients, including HLA matching, induction, maintenance immunosuppressive therapy, and infection prophylaxis, leading to lower incidences of acute rejection and infection, primarily, cytomegalovirus (CMV) infection. 1 The availability of a highly effective oral drug, valganciclovir, is perhaps the primary reason for the growing shift from preemptive therapy to universal CMV prophylaxis. 2 Yet, drug-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In line with this, weaker immunosuppression with cyclosporine A or m-TOR instead of tacrolimus was associated with less CMV infections. The role of immunosuppression was emphasized by Felipe et al, who even observed that previous acute rejection episodes were the major risk factor for CMV infection in the first year after transplantation [26]. Notably, we made both observations as in 60.4% of the cases CMV viremia occurred after rejection, whereas in 39.6% of patients, CMV viremia occurred before rejection.…”
Section: Discussionmentioning
confidence: 50%
“…In line with this, weaker immunosuppression with cyclosporine A or m-TOR instead of tacrolimus was associated with less CMV infections. The role of immunosuppression was emphasized by Felipe et al, who even observed that previous acute rejection episodes were the major risk factor for CMV infection in the first year after transplantation [26]. Notably, we made both observations as in 60.4% of the cases CMV viremia occurred after rejection, whereas in 39.6% of patients, CMV viremia occurred before rejection.…”
Section: Discussionmentioning
confidence: 50%
“…There were no differences in the incidence of CMV infection/disease in patients receiving preemptive therapy, both in the CMV D+/R− high‐risk group and after treatment for AR. In one previous cohort analysis, we showed that 47% of patients treated for acute rejection during the first year after transplantation developed CMV infection/disease [10]. The significant reduction in the incidence of acute rejection in patients receiving rATG induction is therefore associated with lower incidence of CMV infection/disease.…”
Section: Discussionmentioning
confidence: 94%
“…The other patients were monitored at the physician discretion. This targeted strategy was based on the low incidence of CMV disease in this patients receiving AZA [9] but higher incidence after treatment of AR [10]. The preemptive therapy consisted of every other week monitoring the viral replication from the third week after transplantation until the end of the third month, using the CMV pp65 antigenemia assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytomegalovirus (CMV) is a common complication in solid organ transplant recipients, and it can present as a primary infection, secondary infection, or be reactivate from a latent reserve (Koval 2018). In renal transplant recipients (RTR), the incidence of CMV infection or CMV disease (CMVI/CMVD) varies from 17.8%-63.2% (Helantera et al 2014;Chiasakul et al 2015;Corona-Nakamura et al 2009;de Matos et al, 2017;Felipe et al 2019;Ricart et al 2005;Henrique Pinto et al 2016;Minz et al 2020), and its presence is associated with a reduction in glomerular filtration rate (GFR), acute or chronic rejection (AR), opportunistic infection, high cardiovascular risk, and decrease in survival of the graft and the patient (Viot et al 2015;Courivaud et al 2013;Meijers et al 2015;Hodson et al 2013;Stern et al 2014). The following have all been documented as risk factors for CMV: serology test: IgG-positive donor (D) and IgG-negative recipient (D+/R-); anti-rejection therapy; female sex; advanced age; recipients from a deceased donor; transfusions; HLA-B44; absence and/or short lengths of antiviral prophylaxis treatment; and the use of prednisone (PDN), mycophenolate mofetil (MMF), tacrolimus (TAC), belatacept, or anti-thymocyte globulin (ATG) (Felipe et al 2019;Meije et al 2014;Viot et al 2015;ter Meulen et al, 2000;Wagner et al 2015;Futohi et al 2015;Ricart et al 2005;Bataille et al 2010;Chiasakul et al 2015;Diaz et al 2014;Kotton et al 2018;Abou-Ayache et al 2008;Brennan et al 1997;Humar et al 2010;Razonable et al 2001;Lucia et al 2014;Nafar et al 2014;Vacher-Coponat et al 2006;…”
Section: Introductionmentioning
confidence: 99%